Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Sumber Daya Guru Di Sekolah Menengah Pertama Negeri 17 Kota Jambi - Sumirah Sumirah; Rima Wira Tama; Alfina Fristiya Safitri; Muhammad Roihan (Indonesian Journal of Islamic Educational Management, 2025)
This study aims to analyze the role of principal leadership in improving the quality of teacher resources at State Junior High School 17 Jambi City, including leadership roles, inhibiting factors, and implemented strategies. This research employed a qualitative approach conducted at State Junior High School 17 Jambi City. Data were collected through documentation techniques, focusing on teachers’ scientific papers as indicators of teacher resource quality improvement. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings indicate that principal leadership plays a crucial role in enhancing teacher resource quality through functions as a policy maker, motivator, facilitator, and administrator. However, several inhibiting factors were identified, such as differences in teachers’ characteristics, limited technological competence, non-linear academic backgrounds, excessive workloads, lack of training participation, inadequate facilities, and low commitment among some teachers. To address these challenges, the principal implemented various strategies, including encouraging teachers to participate in training programs, seminars, and workshops, strengthening professional and personal competencies, recruiting teachers based on appropriate qualifications, and improving educational facilities and infrastructure. The study concludes that effective and strategic principal leadership has significant implications for improving teacher resource quality and contributes positively to the enhancement of learning quality and overall school performance